2010
DOI: 10.1266/ggs.85.243
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of DNA repair in the hyperthermophilic archaeon, Thermococcus kodakaraensis

Abstract: Extensive biochemical and structural analyses have been performed on the putative DNA repair proteins of hyperthermophilic archaea, in contrast to the few genetic analyses of the genes encoding these proteins. Accordingly, little is known about the repair pathways used by archaeal cells at high temperature. Here, we attempted to disrupt the genes encoding the potential repair proteins in the genome of the hyperthermophilic archaeon Thermococcus kodakaraensis. We succeeded in isolating null mutants of the hjc, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
84
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(92 citation statements)
references
References 63 publications
(77 reference statements)
8
84
0
Order By: Relevance
“…The helicase and nuclease activities of the purified T. kodakarensis Hef protein (TkoHef) for forkstructured DNA was also confirmed in vitro (5). These genetic and biochemical properties of TkoHef suggested that this protein actually works at stalled replication forks in T. kodakarensis by the coordination of its helicase and endonuclease activities, as predicted.…”
supporting
confidence: 56%
See 2 more Smart Citations
“…The helicase and nuclease activities of the purified T. kodakarensis Hef protein (TkoHef) for forkstructured DNA was also confirmed in vitro (5). These genetic and biochemical properties of TkoHef suggested that this protein actually works at stalled replication forks in T. kodakarensis by the coordination of its helicase and endonuclease activities, as predicted.…”
supporting
confidence: 56%
“…Production and Purification of TkoHef-Cloning of the hef gene and preparation of the TkoHef protein were described in detail in our previous report (5). For the preparation of the His-tagged IDR (His-ID), the gene fragment encoding Met 490 -Lys 593 of TkoHef (Hef-ID) was amplified by PCR from T. kodakarensis DNA, using the primer set ID-F/ID-R including NdeI and NotI recognition sequences at their 5Ј-regions (shown in Table 1) for insertion into the NdeI-NotI sites of a modified pET-28a(ϩ) vector (Novagen).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ssDNAbinding proteins of euryarchaeotes resemble eukaryotic replication proteins A (RPA)s whereas those of crenarchaeotes resemble bacterial single-stranded binding proteins (SSBs) (Kerr et al, 2003;Rolfsmeier & Haseltine, 2010). Furthermore, genes for several HR proteins which can be deleted from bacteria and eukaryotes are essential in hyperthermophilic archaea (Fujikane et al, 2010;Zhang et al, 2013), suggesting that, in archaea, these proteins play unusually important roles.…”
Section: Introductionmentioning
confidence: 99%
“…In support to this, a recent genetic analysis of hef mutants in the hyperthermophilic archaeon, Thermococcus Kodakaraensis, has demonstrated that Hef is involved in the repair of a wide variety of DNA damages. In addition, the higher sensitivity of hef mutants to methyl sulfonate and mitomycin C, suggests a central role for Hef protein in the archaeal NER and/or ICL repair pathways (Fujikane et al, 2010).…”
Section: Hefmentioning
confidence: 99%